First diagnosed invasive lobular carcinoma of the breast combined with gastric metastasis and bone metastasis: a case report and review of the literature - Lin Sun; Jiajia Liu; Meng Guo; Jiaqi Xu; Dan Wang (BMC, 2023)
Abstract Rationale Chinese women topped the list of new breast cancers, the first diagnosed gastric metastasis and bone metastasis is extremely infrequent. The clinical and pathological diagnosis of metastatic breast cancer is difficult. To our knowledge, this is the first reported case of the first diagnosis of breast cancer with both gastric metastasis and bone metastasis. Case report The female patient was found to have abdominal distension for 15 days with nausea and vomiting. The patient underwent a gastroscopy at an outside hospital 4 days ago, showing: duodenal bulb changes, gastric retention and chronic non-atrophic gastritis. Gastroscopic biopsy showed chronic inflammation and edema of the duodenal mucosa with glandular hyperplasia. Conservative treatment was given with no relief of symptoms. She was seen in our hepatobiliary and pancreatic surgery department. After admission, palliative surgery was performed, and the swelling and surrounding involved tissues were taken for examination during surgery. The rapid pathological return could not exclude tumor lesions, and the postoperative pathology confirmed the diagnosis of invasive lobular carcinoma of the breast with gastric metastases, and the systemic examination revealed combined bone metastases. Diagnosis Pathology and immunohistochemistry(IHC), a whole-body bone scan confirmed the first diagnosis of breast cancer with both gastric and bone metastases. Interventions Palliative treatment with bisphosphonates and CDK4/6i (Palbociclib) in combination with AI (Exemestane) was administered. Outcomes The patient is currently under regular evaluation and is being followed up.